SOIL REHABILITATION TO INCREASE PRODUCTIVITY BOYOLALI AGRICULTURE BY FAST DETECTION CURCUMARVEL - Dwi Rahmasari Fatmawati; Annisa Kurniawati; Arsyadani Tri Nastiti Nur; Eli Budia Pamilujeng; Praditya Rizqi Novanto; Ratih Ineke Wati (OISAA, 2020)
Boyolali district is one of the areas that has decreased productivity of rice. The decline was due to acidic soil conditions coupled with a lack of awareness of farmers and lack of support for facilities and infrastructure. Basically, to find out the conditions of the soil can be done by detecting the soil using a pH meter. The tool is not widely used because the price is expensive and the farmers care less about the conditions of their paddy fields. The aim of this program is to empower the farming group to be the agent of land rehabilitation through early detection of CurcuMarvel using tumeric. Soil detection devices can be innovated using turmeric. Turmeric that is easily found and familiar among farmers is the solution to the problem of detecting soil conditions. The target was Sari Tani Farming Group located in Suyudan Village , Boyolali Regency. The program involved 10 farmers as the representative of the farmer group. Empowerment programs were conducted by combining several methods, including participatory, discourse, demonstration, and discussion. The activities of CurcuMarvel consist of: (1) transferring information using educational video; (2) demonstrating the soil acidity detection in one of the farmer's paddy fields; (3) land rehabilitation efforts by applying dolomite, manure, and biological fertilizer in the demonstration plot; and (4) turmeric cultivation training in the farmer's yard to prepare the village as the turmeric cultivation center. The outcomes of the program are: (1) the farmers know that their paddy land is acid; (2) the farmers increase their awareness towards the soil acidity effect; (3) the farmers conduct soil rehabilitation; and (4) the farmers have a turmeric center near to the paddy field.